2020
DOI: 10.3390/nu12061814
|View full text |Cite
|
Sign up to set email alerts
|

Uremic Sarcopenia: Clinical Evidence and Basic Experimental Approach

Abstract: Sustained physical activity extends healthy life years while a lower activity due to sarcopenia can reduce them. Sarcopenia is defined as a decrease in skeletal muscle mass and strength due not only to aging, but also from a variety of debilitating chronic illnesses such as cancer and heart failure. Patients with chronic kidney disease (CKD), who tend to be cachexic and in frail health, may develop uremic sarcopenia or uremic myopathy due to an imbalance between muscle protein synthesis and catabolism. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 178 publications
0
34
0
1
Order By: Relevance
“…The mitochondrial dysfunction in human skeletal muscle was also associated with poor physical activity performance when evaluated with a 6-min walk test. This result indicates that uremic sarcopenia is already progressing even before CKD advances ( Nishi et al, 2020 ; Ryan, 2020 ).…”
Section: Mitochondria and Sarcopenia In Ckdmentioning
confidence: 85%
“…The mitochondrial dysfunction in human skeletal muscle was also associated with poor physical activity performance when evaluated with a 6-min walk test. This result indicates that uremic sarcopenia is already progressing even before CKD advances ( Nishi et al, 2020 ; Ryan, 2020 ).…”
Section: Mitochondria and Sarcopenia In Ckdmentioning
confidence: 85%
“…Secondary analysis from the ExTra CKD study showed that supervised physical exercise in CKD patients under conservative therapy is able to significantly improve the volume of the quadriceps femoris [ 150 ]. Furthermore, studies conducted on CKD non-dialysis patients demonstrated that aerobic exercise, intermittent exercise, and resistance training are able to enhance VO 2 peak [ 151 , 152 , 153 ].…”
Section: Other Therapeutic Approaches To Uremic Sarcopeniamentioning
confidence: 99%
“…In addition, uremic sarcopenia has been proposed as skeletal complication, e.g., muscle wasting, in CRF ( Fujita et al, 2006 ). Mitochondrial dysfunction in skeletal muscle in patients with CRF play an important role in promoting the uremic sarcopenia ( Nishi et al, 2020 ). The induced mitochondrial damage can promote inflammation or cause the release of cytochrome; resulting in apoptosis and reduced ATP synthesis leads to cell damage.…”
Section: Discussionmentioning
confidence: 99%